Virtual Force Algorithm and Cuckoo Search algorithm for node placement technique in wireless sensor network - Ahmad, Puteri Azwa (2013)
Wireless Sensor Network (WSN) has become one of the current technologies in the world of information technology.Coverage and connectivity are the main requirement that reflects the performance and quality of services in WSN applications.In WSN applications with a large scale area, the sensor nodes are deployed randomly in a noninvasive way.The deployment process will cause some issues such as coverage hole and overlapping that reflect to the performance of coverage area and connectivity.Node placement model is constructed to find the optimal node placement.Virtual Force Algorithm (VFA) and Cuckoo Search (CS) algorithm approach for node placement technique is analyzed to find the optimal node placement in order to improve the network coverage and connectivity with a minimum coverage hole and overlapping area.